Identifying urban occurrences for cities without open data using web scraping, local news and social media: a case study in Bauru, SP - Ferreira, Felipe Augusto; Souza, Higor Amario de (Anais do Workshop de Computação Urbana (CoUrb); 2026: Anais do X Workshop de Computação Urbana, 2026)
Smart cities, driven by technologies and digital platforms, use data to improve the quality of life for citizens. The lack of data on urban occurrences impairs the identification of problems and the formulation of effective public policies. The city of Bauru, for example, faces challenges in adopting initiatives aimed at data-driven urban management. This work proposes a methodology that uses local information sources, collected through web scraping, to identify urban occurrences. These occurrences are categorized and geolocated, allowing for a spatiotemporal analysis using maps and charts. The methodology supports data-driven decision-making and can be applied to any city that has local information sources. The case study in Bauru points to a large number of occurrences related to infrastructure and crime in the city.